Urgent action to combat climate change and its impacts (SDG 13): transforming agriculture and food systems - Campbell, Bruce M; Hansen, James; Rioux, Janie; Stirling, Clare M; Twomlow, Stephen; (Lini) Wollenberg, Eva (Current opinion in environmental sustainability, 2018)
•Transformative food system actions will be crucial to meet many SDGs.•SDG 13 needs to align with the Paris Agreement.•Actions to reduce food system emissions can have a synergistic effect on several SDGs.•Emission reduction actions can have trade-offs with adaptation and several SDGs.•Transformation in food systems will need technical, policy, capacity enhancement and finance actions Actions on climate change (SDG 13), including in the food system, are crucial. SDG 13 needs to align with the Paris Agreement, given that UNFCCC negotiations set the framework for climate change actions. Food system actions can have synergies and trade-offs, as illustrated by the case for nitrogen fertiliser. SDG 13 actions that reduce emissions can have positive impacts on other SDGs (e.g. 3, 6, 12, 14, 15); but such actions should not undermine the adaptation goals of SDG 13 and SDGs 1, 2, 5 and 10. Balancing trade-offs is thus crucial, with SDG 12 central: responsible consumption and production. Transformative actions in food systems are needed to achieve SDG 13 (and other SDGs), involving technical, policy, capacity enhancement and finance elements. But transformative actions come with risks, for farmers, investors, development agencies and politicians. Likely short and long term impacts need to be understood.